THE POTENTIAL ACTIVITY OF COMBINATION OF QUERCETIN COMPOUND WITH TURMERIC EXTRACT ENCAPSULATED BY CHITOSAN NANOPARTICLES AS ALTERNATIVE THERAPY FOR DIABETES MELLITUS: A LITERATURE REVIEW - Muhammad Rifqi Al Azim Rifqi (Yayasan Pendidikan Medika Indonesia, 2025)
Diabetes mellitus (DM) is a metabolic disease that threatens global health today. This metabolic disorder can cause microvascular and macrovascular complications. Method: This study used a Literature Review design. The study was conducted by searching the internet using a journal search engine. The journal search engines used in this study include Pubmed, Science Direct, with the keywords: